Data on the species composition and the distribution of harmful marine epiphytic microalgae living on coral reefs in the Noth Vietnam - Thuoc, Chu Van (Academia Journal of Biology, 2015)
Data on the species composition and the distribution of harmful marine epiphytic microalgae living on coral reefs in the Noth Vietnam